2017
DOI: 10.1111/1440-1681.12702
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Na+ intake induces renal function injury in rats prevented by a short‐term angiotensin converting enzyme inhibitor

Abstract: The Na -ATPase, a secondary pump in the proximal tubule, is only weakly responsive to angiotensin II in adult offspring exposed perinatally to high Na intake. We have investigated whether the offspring from mothers given 0.3 mol/L NaCl show an ineffective angiotensin II action to increase in blood pressure. It was hypothesized that functional alterations at adult life are associated with the number of angiotensin II-positive cells in the developing kidney, with increased oxidative stress in maternal/foetal org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…With respect to oxidative stress (Figure ), saline decreased basal O 2 − production in the heart with no influence in kidneys, which matches with the lack of renal and tissular systemic oxidative lesions in the offspring whose mothers given saline overload during gestation . The observations regarding NADPH oxidase‐stimulated formation of O 2 − , stimulated by α‐Tocopherol in the heart but not in the kidney (regardless of the type of maternal liquid intake), suggest that the cardiac and renal actions of α‐Tocopherol do not involve the same mechanisms.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…With respect to oxidative stress (Figure ), saline decreased basal O 2 − production in the heart with no influence in kidneys, which matches with the lack of renal and tissular systemic oxidative lesions in the offspring whose mothers given saline overload during gestation . The observations regarding NADPH oxidase‐stimulated formation of O 2 − , stimulated by α‐Tocopherol in the heart but not in the kidney (regardless of the type of maternal liquid intake), suggest that the cardiac and renal actions of α‐Tocopherol do not involve the same mechanisms.…”
Section: Discussionmentioning
confidence: 52%
“…Modifications in the RAS for a short period just before or after weaning can change renal function in the longer term. Inhibition of RAS for short periods is sufficient to decrease blood pressure in SHR, as well as to the recovery of the normal activities of Na + ‐transporting ATPases in the renal proximal tubule and the control values of creatinine clearance (CrCl) in the offspring from mothers given salt overloading during gestation . A central role for RAS in the cardiovascular and renal effects of α‐Tocopherol received support in one of our studies, in which we demonstrated that maternal α‐Tocopherol during gestation programs retarded renal development in the pups (enlargement of the nephrogenic zone in kidneys of 1‐day‐old pups), as well as for altered expression of several components of the local renin/angiotensin system in both pups and juvenile rats (upregulation of Ang II receptors (AT 1 R and AT 2 R) and of several isoforms of PKC, a key element of AT 1 R‐linked signalling pathways) .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation